STRATEGI PENGELOLAAN SAMPAH BERBASIS MASYARAKAT (STUDI KASUS DI BANK SAMPAH NURI LESTARI SERASI) - Ida Bagus Suryatmaja; Ni Gst. Ag. Gde Eka Martiningsih; I Made Nada (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
Independently waste management is expected to be one real way to solve the garbage problem. Garbage today remains a national problem. This is due to very low public awareness of the litter problem. The starting point of good waste management and the right is originated from households, as household waste is generated every day continuously. Other garbage bins dalah market, which requires merchants keaadaran management. From the analysis of the situation which is intended to provide a picture or map of clues to the location and boundaries of science and technology For Region (IBW) and the description of the existing condition of the area relevant to the issues to be addressed. IBW region located in Tabanan regency which is one of the districts in the province of Bali in addition to seven counties and one city to another, namely Jembrana, Buleleng, Karangasem, Klungkung, Bangli, Gianyar, Badung and Denpasar. Based on the results of hearings with Tabanan District Government through the Regional Development Planning Board (Bappeda), the direction of development of Tabanan is a balance between environmental sustainability efforts functions with efforts to use natural resources in order to achieve prosperity for the people of Tabanan particular. Availability of natural resources are limited and uneven in the district both quantity and quality to encourage the Government in Tabanan Kabuptaen strongly consider the use of natural resources. With waste management as a group is expected to build revenue (income generating) for the community that can indirectly improve the welfare of the community.